Directional sound transmission using ultrasonic array - Tan, Desmond Jun Quan (Nanyang Technological University, 2022)
High power non-lethal acoustic hailing devices are used for directional acoustic air transmission to incapacitate targets at a distance and are engaged in military, homeland security and law enforcement operations. A previous project study demonstrated two beams directional acoustic air transmission, with an array of commercial 40 kHz piezoelectric ultrasonic transducer and narrow frequency bandwidth of about 2.5kHz, showing limited audible sound fidelity needed for directional communication.